Tinjauan Koreografi Tari Tabuik di Sanggar Seni Mustika Minang Kota Pariaman - Nabila Putri Chania; Darmawati Darmawati (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
This study aims to describe and reveal the Review of Tabuik Dance Choreography at Mustika Minang Art Studio in Pariaman City. This type of research is qualitative with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments stationery, cameras and gadgets / smartphones. Data were collected through literature study, observation, interviews and documentation. The steps of analyzing data are collecting data, describing the data and inferring the data. The results showed that this Tabuik dance has 3 parts, namely the beginning as the opening of the dance, the middle, and the end as the climax. In this Tabuik dance there are elements of dance composition consisting of; motion, floor design, group composition, top design, dancers, music design, costumes and makeup as well as props. The movements worked on by the choreographer were taken from the traditional procession carried out at the time of making Tabuik itself. This dance work also looks very interesting with floor patterns and diverse group compositions so that the audience does not get bored in watching the performance and dancers who master strong movements and movements. The costumes used in the Tabuik dance are simple costumes. This Tabuik dance raised the theme of the Hoyak Tabuik procession in Pariaman City.The music that accompanies the dancer's movements uses a fast tempo to the end of the dance with dang singing. The property used in Tabuik dance is the miniature Tabuik itself.